Tax System Modernization and Incentive Policies' Impact on Taxpayer Compliance in Motor Vehicle Tax E-Payment - Patriandari Patriandari; Moh Abdurrosyid; Liestiani Dyahningrum (Quantitative Economics and Management Studies, 2022)
This study aims to determine the influence of modernization of the tax administration system and tax incentive policies on the compliance of motor vehicle taxpayers in Bekasi City. This research approach is a quantitative research using primary data through the distribution of questionnaires. The sampling technique of this study was purposive sampling with a total sample of 100 respondents. The data analysis technique of this study uses the Partial Least Square (PLS) technique with the help of the SmartPLS 3.0 program. The results showed that the modernization of the tax administration system and tax incentive policies had a positive effect on the compliance of motor vehicle taxpayers. This is because when the government imposes social isolation policies and outdoor activity restrictions amid a pandemic, the online system put in place may be a solution for taxpayers. This is because the motor vehicle tax bleaching program is very advantageous for vehicle taxpayers, particularly for taxpayers who have arrears or fines from late vehicle tax payments.